ANALISIS PENENTUAN HARGA POKOK PRODUKSI PADA PERUSAHAAN GARAM BERYODIUM (Studi Kasus pada UD. Empat Mutiara) - Lundu Bontor Sihite; Sudarno Sudarno (Diponegoro Journal of Accounting, 2012)
The purpose of this study is to evaluate the implementation of company policies that have been specified in the determination of the cost of production. Cost of production should be doing using the cost of processing method. This method is collecting cost of production of the period by departement or cost center.. This study was conducted using the method of data collection, by interviews with corporate leaders to find out weaknesses in the calculation of the cost production in the company. For the analytical methods author used the comparative method, which comparing the problem. Author compared implementation of company policies about cost of production with references from literature to recommend to the company. The results showed that in the determination of the cost of production, the company has made a report the cost of production but still not quite right. The authors suggest companies determine the cost of production by using the Cost of Process. Where each department or cost center to account for all costs that occurred in each cost center. The company fits using this method because the company produces a homogeneous product in very large kuota